MODAL MANUSIA DAN MODAL FISIK PADA USAHA MIKRO TAHU DI DESA LAMBUSA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Alfan, La Ode Muhammad; Batoa, Hartina; Jayadisastra, Yoenita (Universitas Halu Oleo, 2024)
The objective of this study is to ascertain the extent to which human and physical capital are deployed in tofu processing micro-enterprises in Lambusa Village, Konda Sub-district, South Konawe Regency. The population under investigation comprises all individuals employed in tofu processing businesses in Lambusa Village. The sample was determined using the census method, namely by taking the entire number of the study population, so that the sample in this study was 33 people (30 employees and 3 tofu business owners). This type of research employs a quantitative approach. Research data were collected using survey methods, interviews, and documentation, with the assistance of media in the form of questionnaires. Then the research data were analyzed using the quantitative descriptive method, using the class interval formula. The findings indicated that human capital and physical capital in tofu processing micro-enterprises in Lambusa Village were notably high. This suggests that the existing capital is capable of providing and contributing to the maintenance and increase in tofu production. Human capital encompasses knowledge, expertise, abilities, and skills, each of which is generally in the high category. The human capital possessed by employees of tofu processing businesses is derived from the experience they have accumulated over the years working in tofu processing businesses. The physical capital of tofu processing micro-enterprises encompasses both working capital and fixed capital, both of which are typically classified as high.